MicroRNA-1912 regulates cholesterol homeostasis by targeting PCSK9 - Chan Joo Lee; Myeongjune Go; Sae-Bom Jeon; Sun-Ho Lee; Dongkook Min; So Hee Park; Seunghyun Lee; Sahng Wook Park (Molecular Therapy: Nucleic Acids)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to low-density lipoprotein (LDL) receptor (LDLR) and promotes degradation of LDLR, regulating cholesterol homeostasis. Previous studies have reported several microRNAs (miRNAs) that regulate PCSK9 expression; however, evidence for these effects in animal models remains controversial. This study aimed to explore miRNA candidates for PCSK9 regulation and to validate the most potent miRNA for this regulation in vivo. Bioinformatic algorithms identified miRNAs regulating PCSK9, with miR-224 and miR-1912 showing a high probability of targeting PCSK9. Treatment with miR-224 and miR-1912 significantly reduced PCSK9 mRNA and protein levels and led to an increase in LDLR protein expression, resulting in increased uptake of LDL particles in HepG2 cells, with miR-1912 showing a greater effect than miR-224. Specific interactions of miR-1912 and miR-224 with the 3′ untranslated region (UTR) of PCSK9 mRNA were confirmed by a luciferase reporter assay and site-directed mutagenesis analysis of the predicted seed region. In transgenic mice expressing liver-specific human PCSK9 with its 3ʹ UTR, administration of miR-1912 mimics resulted in a reduction of plasma total cholesterol levels as determined by fast protein liquid chromatography following hepatic delivery. These findings highlight miR-1912 as a promising therapeutic candidate for hypercholesterolemia via targeted, post-transcriptional regulation of PCSK9.